A new species of Craterellus (Cantharellales, Hydnaceae) from Guizhou Province, China - Zhang, Jing; Wu, Di; Deng, Chun Ying; Zhang, Ming; Dauner, Lucas; Wijayawardene, Nalin N. (Phytotaxa, 2020)
Craterellus albidus is proposed as a new species based on both morphological evidence and DNA analyses. Morphologically, Cr. albidus is characterized by its small-sized whitish pileus, smooth to slightly folded hymenium, white to lemon-yellow stipe, ellipsoid to broadly ellipsoid basidiospores with a size of 7.8–11 × 6.1–8.2 µm, and a cutis pileipellis. Phylogenetic analyses based on the nuclear ribosomal internal transcribed spacer (ITS) regions and the large subunit ribosomal RNA (nrLSU) region provide further evidence that the described specimens represent a new species.